Shifting Welfare Policy Positions: The Impact of Radical Right Populist Party Success Beyond Migration Politics - Werner Krause; Heiko Giebler (Representation, 2020)
Political parties respond strategically to the electoral success of radical right populist parties (RRPPs). While previous research has focused on programmatic responses on cultural conflict issues, we are expanding the research on policy position adaption to the economic left-right issue of welfare-state politics. Actual and potential supporters of RRPPs do not only feel threatened by migration or liberal conceptions of society but are also often confronted with real or perceived socio-economic decline. Therefore, we argue that established parties do not only react by changing their socio-cultural policy offers but also by adjusting their welfare state policy positions. Based on parties' voter potentials and issue ownership theory, we investigate whether such changes are especially pronounced for left-of-center parties. Analysing data from 18 West European countries since 1985, we find that non-RRPPs indeed advocate more leftist positions on welfare state policies in response to increasing electoral support for RRPPs. This effect is especially pronounced for economically left-of-centre parties as these parties might consider this to be a promising strategy to win back voters from the populist radical right.
https://doi.org/10.7910/DVN/KUNWOP
Keywords: 330; radical right populist parties; party competition; welfare; party positions; left-right